MORPHOLOGICAL IDENTIFICATION OF WILD EDIBLE MUSHROOM (Termitomyces striatus) AT IPB UNIVERSITY CAMPUS FOREST - Nurhakiki Nurhakiki; Ivan Permana Putra (Universitas Islam Negeri Ar-Raniry, 2024)
Indonesia is a tropical country which is famous for its 2 seasons, namely the rainy season and the dry season. In the rainy season, the humidity level will increase and induce the development of mushroom’s fruiting body, including the edible kind. The research on wild edible mushroom diversity should be carried out massively in various regions in Indonesia. One of the potential areas is the forest area of the IPB University Campus (HKIU). This study aims to explore and identify wild edible mushroom in HKIU. The mushroom exploration was done using an opportunistic sampling method. Selected wild mushroom was obtained and identified for macroscopic and microscopic morphological characters. The identification results based on the morphological characters of the fruiting bodies indicated that the mushrooms obtained from the current study is Termitomyces striatus which is acknowledged as an edible mushroom. Our finding can provide the additional information on distribution of T. striatus in Indonesia and the potential of this mushroom cultivation in foreseeable future.